2020
DOI: 10.1108/ajems-03-2019-0110
|View full text |Cite
|
Sign up to set email alerts
|

Cash crops financing, agricultural performance and sustainability: evidence from Nigeria

Abstract: PurposeOne of the challenging factors in achieving sustainable growth is the inability of the Nigerian government to diversify the country's revenue base. This study aims to investigate the relationship between cash crop financing and agricultural performance in Nigeria.Design/methodologyFour crops were considered, namely, cotton, cocoa, groundnut and palm oil. The impact of cash crop finance shock on agricultural performance was investigated using the vector error correction model (VECM), while the long-run r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 46 publications
(56 reference statements)
1
29
1
Order By: Relevance
“…The growth rate for electricity consumption is very germane for business performance. This is in line with the United Nations Sustainable Development Goals 7, 9, 11 and 12 (United Nations, 2015;Asaleye et al, 2020). This goals have important implication on business performance because lack of electricity supply will lead to over reliance on alternative source of energy which can be more expensive, like solar, coal, generator.…”
Section: Introductionsupporting
confidence: 64%
“…The growth rate for electricity consumption is very germane for business performance. This is in line with the United Nations Sustainable Development Goals 7, 9, 11 and 12 (United Nations, 2015;Asaleye et al, 2020). This goals have important implication on business performance because lack of electricity supply will lead to over reliance on alternative source of energy which can be more expensive, like solar, coal, generator.…”
Section: Introductionsupporting
confidence: 64%
“…This proposition was hatched around 1883. Ever since the unveiling of this proposition, followers of this view have expressed mixed opinions (Gatsi et al, 2019;Manyeki and Kotosz, 2017;Keho, 2017;Lawal et al, 2020;Asaleye et al, 2020;Lawal et al, 2019;Babajide et al, 2020;Olanrele et al, 2020;Aktan, 2017;Ifeyinwa, Idenyi, Chibuzor & Agbi, 2016;Eze, 2016;Salwindi and Seshamani, 2016;Dahunsi et al, 2019;Moore, 2016;Atasoy and Gur, 2016;Ampah and Kotosz, 2016;Magazzino et al, 2015;Funashima, 2015). Among early versions that propelled dichotomization of WP are that of Peacock and Wiseman (PW) (1961), Musgrave (1969), Gupta (1967), Goffman (1968), Peacock & Wiseman shared version (1967), among others; each explaining its own version of the proposition based on their scholarly standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Kolawole (2013) investigated the connection among institutional reforms, interest rate policy and agricultural sector financing using the error correction mechanism (ECM). Even though studies were carried out in relation to the agricultural sector, most of these studies ignored the effect of the monetary policy channels identified in the literature (Aremu et al, 2019;Asaleye, Alege, Lawal, Popoola, & Ogundipe, 2020;Popoola., Alege, Gershon, & Asaleye, 2019). Other studies, such as that by Oboh et al (2019), investigated monetary policy's effect on agricultural sector performance in Nigeria using the autoregressive distributed lag approach.…”
Section: Introductionmentioning
confidence: 99%